2023
DOI: 10.1111/jora.12837
|View full text |Cite
|
Sign up to set email alerts
|

Relations between social withdrawal subtypes and socio‐emotional adjustment among Chinese children and early adolescents

Abstract: The aim of the present study was to compare the relations between subtypes of social withdrawal and socio‐emotional adjustment in Chinese children and early adolescents. Participants included 571 children (Mage = 9.62 years) and 345 adolescents Mage = 12.12 years) in mainland China. Social withdrawal subtypes (i.e., shyness, unsociability, social avoidance) and indices of socio‐emotional adjustment were assessed via self‐reports, peer nominations, and teacher ratings. Shyness tended to be more strongly associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 94 publications
3
4
0
Order By: Relevance
“…Of course, these are only speculations, and well‐designed research with a priori hypotheses is needed to formally test these speculations. Nonetheless, together with recent findings in China (Ding et al., 2023; Hu et al., 2022), these results provide preliminary support to the proposed developmental model of unsociability and the potential constructive function of spending time alone in early adolescence (Coplan et al., 2019).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Of course, these are only speculations, and well‐designed research with a priori hypotheses is needed to formally test these speculations. Nonetheless, together with recent findings in China (Ding et al., 2023; Hu et al., 2022), these results provide preliminary support to the proposed developmental model of unsociability and the potential constructive function of spending time alone in early adolescence (Coplan et al., 2019).…”
Section: Discussionsupporting
confidence: 81%
“…Thus, unsociability is expected to elicit negative perceptions like other subtypes of social withdrawal, yet the present results did not support this proposition. Instead, the results aligned with findings from primarily Western societies and a few recent studies in China that unsociability may not pose similar risks as shyness or social avoidance into late adolescence and emerging adulthood (Closson et al, 2022;Coplan et al, 2019;Ding et al, 2023;Hu et al, 2022;Nelson, 2013).…”
Section: Adolescents' Perceptions Of Socially Withdrawn Peerssupporting
confidence: 82%
“…The present meta-analysis found significant and positive associations between unsociability and peer problems in Chinese children and adolescents, which is consistent with previous empirical findings in Chinese culture [44,46,[48][49][50]58]. Compared to the cross-cultural meta-analysis regarding the associations between social withdrawal and peer problems [51], the strength of the correlation coefficient was higher in the present study.…”
Section: Overall Associations Between Unsociability and Peer Problems...supporting
confidence: 91%
“…Although previous studies found the positive associations between unsociability and peer problems in Chinese culture [48][49][50], the strength and direction of these associations were mixed and no study has synthesized the previous findings to examine the associations in Chinese sample. Ran and colleagues conducted a meta-analysis to assess the associations between three subtypes of social withdrawal and peer problems in Chinese and North American youth to detect the mixed results in Western countries and China [51].…”
Section: The Present Studymentioning
confidence: 96%
See 1 more Smart Citation